Bargaining end customer prices for supply chain coordination in a declining price sensitive market. Issue 1 (2nd January 2017) - Modak, N.M.; Panda, S.
Abstract : In a two-echelon supply chain with declining price sensitive demand, if a buyer has the freedom to set the end customer prices and the number of replenishments over a finite time horizon, then he/she chooses these two so as to ensure his/her own profit maximization. But the buyer's optimal operating policy does not lead to the supplier's profit maximization. Typically in this situation a coordination scheme may suggest a particular contract form that results in a win–win situation for participating parties in the supply chain. If the buyer is rational, then he/she has no incentive to deviate from his/her own operating policy. To induce the buyer to deviate from his/her optimal operating policy, the supplier may propose a side payment to the buyer through bargaining instead take the opportunity to set (i) alternative end customer prices and buyer's replenishment number or (ii) alternative end customer prices based on the buyer's proposed replenishment number. We examine whether such supplier dominated optimal policies lead to first best end customer prices or not. We also examine the relationship between two replenishment numbers and side payments for these two centralized systems. The proposed model is illustrated by numerical examples.